2017
DOI: 10.1088/1748-9326/aa8f55
|View full text |Cite
|
Sign up to set email alerts
|

Remotely sensed predictors of conifer tree mortality during severe drought

Abstract: Widespread, drought-induced forest mortality has been documented on every forested continent over the last two decades, yet early pre-mortality indicators of tree death remain poorly understood. Remotely sensed physiological-based measures offer a means for large-scale analysis to understand and predict drought-induced mortality. Here, we use laser-guided imaging spectroscopy from multiple years of aerial surveys to assess the impact of sustained canopy water loss on tree mortality. We analyze both gross canop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 27 publications
1
48
0
Order By: Relevance
“…Future investigations coupling field measurements of LAI and hyperspectral imagery could refine the characterization of drought resistance. We note that drought response strategies are species specific as are the corresponding CWC changes (Brodrick & Asner, ). The second explanation for resistance is access to alternate (not direct precipitation) sources of water.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Future investigations coupling field measurements of LAI and hyperspectral imagery could refine the characterization of drought resistance. We note that drought response strategies are species specific as are the corresponding CWC changes (Brodrick & Asner, ). The second explanation for resistance is access to alternate (not direct precipitation) sources of water.…”
Section: Discussionmentioning
confidence: 89%
“…At the landscape level, remotely sensed CWC has been linked to site‐specific water balance (Paz‐Kagan et al, ) and is related to ground‐level measurements of foliage dieback (Martin et al, ), suggesting that changes in LAI are a dominant contributor to changes in CWC. Analyzed through time, changes in CWC provide an indication of forest vulnerability (Asner et al, ) and mortality (Brodrick & Asner, ) in response to drought.…”
Section: Introductionmentioning
confidence: 99%
“…Using airborne lidar and canopy spectroscopy and satellite-based models, Asner et al (2016) revealed progressive forest canopy water loss during the recent California drought. Another remote sensing-based study by Brodrick and Asner (2017) reported a close relationship between sustained canopy water loss and mortality in conifers over the Sierra Nevada mountain range in California. Satellite-derived Normalized Difference Vegetation Index (NDVI) data have long been used to monitor the impacts of drought on vegetation greenness, which is sensitive to soil moisture conditions and precipitation (Gu et al, 2007(Gu et al, , 2008Karnieli et al, 2010;Kogan, 1995;Pettorelli et al, 2005;Reed et al, 1994;Williams et al, 2013).…”
Section: Introductionmentioning
confidence: 95%
“…Recent conifer mortality episodes on a large spatial scale have occurred throughout the western USA and Canada (Auclair et al, 1990;Allen et al, 2010), highlighting the vulnerability of today's mountain forests. Also, new research has helped identify the underlying physiological mechanisms that will lead to greater tree mortality in a warmer, drier environment (Breshears et al, 2005;Pyatt et al, 2016;Brodrick and Asner, 2017;Choat et al, 2018). Yet, despite over 100 years of investigation, large gaps still persist in our understanding of how mountain forests function at the mechanistic level, particularly at high elevation.…”
Section: Introductionmentioning
confidence: 99%